PELATIHAN PEMBELAJARAN MENGENAL HURUF MENGGUNAKAN MEDIA PUZZLE DI PAUD AL-HIDAYAH DESA BANJAR - Herawati, Tuti; Sudarti, Nila; Kalsum, Umi (Smart Education, 2025)
Abstract: This study aims to determine the effectiveness of using puzzle media to improve the ability to recognize letters in children of PAUD Al-Hidayah, Banjar Village. The method used in this study is classroom action research which is carried out in two cycles. The number of children in this study was 35 students. The implementation of using puzzle media has been carried out and is running well. Children at PAUD Al-Hidayah, Banjar Village have been able to mention the symbols of letters they know and the shape of letters. The results of this study indicate that learning with puzzle media has an increase in the percentage value of the ability to recognize letters, namely, in the initial condition of 35.70%. Then in cycle 1 the average percentage increased to 61.10%, and the average percentage in cycle II was able to increase to 83.73%. From the data above, it is clear that puzzle media can improve the ability to recognize letters in Early Childhood. Keywords: Puzzle Media, Recognizing Letters, Early Childhood.